Neuronal survival of DRG neurons after neurite transection in vitro promotes by nerve growth factor and brain derived neurotrophic factor - Kaval Oğuz, Elif (Cellular and Molecular Biology, 2018)
Neurotrophic factors are growth factors that promote neuronal survival, regulate synaptic function and neurotransmitter release, and promote the plasticity and growth of axons in the peripheral and central nervous systems. This study focused on the roles of nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) in the survival of adult dorsal root ganglion (DRG) neurons following axotomy. To investigate this, we cultured adult mouse DRG neurons and administered NGF or BDNF to the culture medium at different doses before transection. After determining the optimal doses of NGF and BDNF, these factors were then applied in combination. Axotomy was performed using a precise laser beam and neuronal death was visualized through cell observer microscopy system, by adding propidium iodide to the culture medium. The results demonstrate that the optimal doses of NGF and BDNF for neuronal survival are 150 ng/mL and 50 ng/mL, respectively. The highest level of neuronal survival was observed in the cells treated with a combination of NGF and BDNF. In conclusion, NGF and BDNF have a positive effect, both individually and in combination, on the survival of DRG neurons following neurite transection.